2017
DOI: 10.2147/jpr.s142147
|View full text |Cite
|
Sign up to set email alerts
|

Intrathecal pain management: a team-based approach

Abstract: ObjectivePhysician assistants (PAs), nurse practitioners (NPs), and registered nurses (RNs) provide professional services on pain management teams. This review provides an overview of the practical management of chronic pain with intrathecal (IT) therapy using an interprofessional approach (eg, physicians and other health care professionals), with a focus on the contributions of PAs, NPs, and RNs.MethodsNarrative review based on literature searches of the Medline database and treatment guidelines on the use of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 62 publications
0
16
0
Order By: Relevance
“…6 Concerns regarding complications impede the further dissemination of IMITPP. 22,27 Although intrathecal morphine infusion therapy reduces the incidence of the adverse advents caused by systemic opioids due to high morphine concentrations at the site of action, several operative and drug-related complications may arise after implantation. 3,4 As compared to intrathecal morphine infusion therapy via an implanted morphine pump, disadvantages of IMITPP in operative complications are infection and the possibility of inadvertent catheter dislodgement or removal, which could be avoided by careful maintenance and was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Concerns regarding complications impede the further dissemination of IMITPP. 22,27 Although intrathecal morphine infusion therapy reduces the incidence of the adverse advents caused by systemic opioids due to high morphine concentrations at the site of action, several operative and drug-related complications may arise after implantation. 3,4 As compared to intrathecal morphine infusion therapy via an implanted morphine pump, disadvantages of IMITPP in operative complications are infection and the possibility of inadvertent catheter dislodgement or removal, which could be avoided by careful maintenance and was not observed in this study.…”
Section: Discussionmentioning
confidence: 99%
“…We considered diarrhea as a gastrointestinal withdrawal symptom associated with systemic opioids withdrawal in the two patients. 27 Additional studies examining factors associated with risks of gastrointestinal withdrawal symptom are required.…”
Section: Discussionmentioning
confidence: 99%
“…21,23 Previous observations demonstrate that N-type VDCCs blockers result in analgesia in a range of pain models, 17,31,55 and ziconotide, the first-choice compound among ω-CTX analogues, is in clinical use as an intrathecal medication for chronic pain in the United States. 1,2 Of note, a direct block of N-type Ca 2+ channels, as that achieved by ziconotide or ω-CTXs, is associated with serious side effects (psychological and neuropsychiatric symptoms including depression, cognitive impairment, and hallucinations; anxiety; panic attacks; ataxia; asthenia; headache; and dysesthesia). 35 Interestingly, an "indirect" VDCC modulation as that accomplished by A 3 AR activation could represent a suitable approach to pain control without adverse side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Other clinical factors that have been reported to influence outcomes include duration of symptoms (duration less than 3 months is associated with better outcomes), present functional status, socio-economic status, psychological factors like depression and anxiety, and sleep quality. 19,70,71 Kanna et al 36 reported that clinical factors including significant sensory symptoms, high mean pre-injection ODI score, high mean post-injection score at 3 weeks, and white-collar employment were associated with poor outcomes following SNRB.…”
Section: Prognostic Indicatorsmentioning
confidence: 99%